The Effect of Self-Service Technology on Customers’ Trust and Loyalty (Case Study at Terminal 3 Self-Service Technology Soekarno-Hatta International Airport) - Ramos Purba; Yevis Marty Oesman; Rita Komaladewi (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of self-service technology (SST) on customer’s trust and loyalty at PT. Angkasa Pura II (Persero) by taking the object of study at Terminal 3 of Soekarno-Hatta International Airport. This study uses service performance report data and self-service complaint reports for the period 2019 and 2020 to February 2020. The research method in this study is a quantitative method with SEM analysis tools - Partial Least Square (PLS). The results show that self-service technology (SST) has a significant effect on customer’s trust. Self-service technology (SST) does not necessarily have a direct and significant effect on customer’s loyalty, but through new customer’s trust, it is able to increase customer’s loyalty. The results show that customer’s trust has a significant effect on customer’s loyalty. The increase in customer’s loyalty is occurred in line with the increasing trust of PT. Angkasa Pura II (Persero) customers in the quality of the performance of self-service operating services at the airport.